Uji Aktivitas Ekstrak Etanol Kulit Durian (Durio zibethinus Murr.) Terhadap Bakteri Propionibacterium acnes dan Staphylococcus aureus - Safitri, Andi Tendriani; -, Ismail; Adiratna, Nur; Adiratna, Nur; Drajat, Sakiah; Drajat, Sakiah (Jurnal Farmasi Udayana; Vol. 11, No. 1, Tahun 2022, 2022)
Acne is a skin disease that teenagers often complain about at this time. The bacteria that are one of the causes of acne are Propionibacterium acne, Staphylococcus aureus, and Staphylococcus epidermidis. Durian skin (Durio zibethinus Murr) is used as a treatment. Durian  contains secondary metabolites, namely flavonoids which have antibacterial activity. Extracts obtained by maceration using 70% ethanol. The phytochemical test shows that durian  contains flavonoids as anti-bacterial compounds so that durian skin can be used as an alternative active ingredient in making anti-acne gel preparations. The ethanol extract of durian  was then tested for activity by making 3 series concentrations of 10%, 15%, 25% which were then tested on Propionibacterium acne and Staphylococcus aureus bacteria. The results showed that with a concentration of 10%, 15%, 25% with Propionibacterium acne test bacteria had a inhibition zone with a diameter of 7.5 mm ± 0.4 mm (10%), 7.7 mm ± 0.3 mm (15%), 8.4 mm ± 0.2 mm (25 %) and using Stphylococcus aureus test bacteria has a inhibitory zone with a diameter of 8.11 mm ± 0.4 mm (10%), 8.11 mm ± 0.3 mm (15%), 8.8 mm ± 0.5mm(25%).